2017
DOI: 10.1016/j.energy.2017.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of flow around a single and two in-line horizontal-axis wind turbines

Abstract: A Large Eddy Simulation (LES) has been employed in order to study the flow field in a single-wind turbine and in two in-line wind turbines. The present study focuses on the flow around a horizontal axis wind turbine in a virtual wind tunnel. The anisotropic residual stress tensor is driven by the Smagorinsky model. The results are consistent with experimental data presented in literature. Streamwise velocity is increased and cross stream velocity is decreased as wake moves in downstream direction. A faster rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Kuo 18 identified SS as the most accurate among the methods. However, Chamorro 19 found that the wake recovery speed of two wind turbines with an in-line setup is sometimes higher than that of a single wind turbine. Meanwhile, the SS method leads to a deficit in the mixed-wake velocity, which must be higher than that of the single unit.…”
Section: Introductionmentioning
confidence: 99%
“…Kuo 18 identified SS as the most accurate among the methods. However, Chamorro 19 found that the wake recovery speed of two wind turbines with an in-line setup is sometimes higher than that of a single wind turbine. Meanwhile, the SS method leads to a deficit in the mixed-wake velocity, which must be higher than that of the single unit.…”
Section: Introductionmentioning
confidence: 99%
“…The class of CFD methods has the potential to provide the most consistent and physically realistic solution of the wind turbine flow field. Veisi and Mayam 38,39 employed large eddy simulation to study the effect of rotation direction of the downstream turbine in a two in-line setup. The results showed good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…3 The unsteady aerodynamic performance of floating wind turbine has been studied with both experimental and numerical methods. 7,26 With the improvement of computational fluid dynamic (CFD) methods based on solving Navier-Stokes flow functions and computational resources, CFD have been widely used for the aerodynamic performance study of wind turbines such as the wind turbine blades tower interaction by Janajreh et al; 27 the detailed flow mechanism at the inboard region of the blade was analyzed by Bangga et al; 28 and the aerodynamic interaction between the rotor wake and the wind farm terrain was analyzed by Nedjari et al, 29 Veisi and Mayam 30,31 and Miao et al 32 CFD simulation on floating wind turbines has been applied, [33][34][35][36][37][38] which can provide detailed flow field characteristics of the floating wind turbines under platform motions.…”
Section: Introductionmentioning
confidence: 99%
“…; 27 the detailed flow mechanism at the inboard region of the blade was analyzed by Bangga et al. ; 28 and the aerodynamic interaction between the rotor wake and the wind farm terrain was analyzed by Nedjari et al., 29 Veisi and Mayam 30,31 and Miao et al. 32…”
Section: Introductionmentioning
confidence: 99%